Six1 is essential for differentiation and patterning of the mammalian auditory sensory epithelium - Zhang, Ting; Xu, Jinshu; Maire, Pascal; Xu, Pin-Xian (PLoS genetics, 2017)
The organ of Corti in the cochlea is a two-cell layered epithelium: one cell layer of mechanosensory hair cells that align into one row of inner and three rows of outer hair cells interdigitated with one cell layer of underlying supporting cells along the entire length of the cochlear spiral. These two types of epithelial cells are derived from common precursors in the four- to five-cell layered primordium and acquire functionally important shapes during terminal differentiation through the thinning process and convergent extension. Here, we have examined the role of Six1 in the establishment of the auditory sensory epithelium. Our data show that prior to terminal differentiation of the precursor cells, deletion of Six1 leads to formation of only a few hair cells and defective patterning of the sensory epithelium. Previous studies have suggested that downregulation of Sox2 expression in differentiating hair cells must occur after Atoh1 mRNA activation in order to allow Atoh1 protein accumulation due to antagonistic effects between Atoh1 and Sox2. Our analysis indicates that downregulation of Sox2 in the differentiating hair cells depends on Six1 activity. Furthermore, we found that Six1 is required for the maintenance of Fgf8 expression and dynamic distribution of N-cadherin and E-cadherin in the organ of Corti during differentiation. Together, our analyses uncover essential roles of Six1 in hair cell differentiation and formation of the organ of Corti in the mammalian cochlea.